2012
DOI: 10.1038/ncomms2056
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of an inhibitory restraint of seizure activity in humans

Abstract: The location and trajectory of seizure activity is of great importance, yet our ability to map such activity remains primitive. Recently, the development of multi-electrode arrays for use in humans has provided new levels of temporal and spatial resolution for recording seizures. Here, we show that there is a sharp delineation between areas showing intense, hypersynchronous firing indicative of recruitment to the seizure, and adjacent territories where there is only low-level, unstructured firing. Thus, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

64
570
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 406 publications
(638 citation statements)
references
References 44 publications
64
570
4
Order By: Relevance
“…SUA activities during ictal events were also less hypersynchronous as was previously hypothesized (Babb et al, 1987;Truccolo et al, 2011). Detailed analysis of ictal unit firing revealed the presence of an inhibitory wave local to the seizure onset zone , suggesting that inhibitory input may prevent the spread of the seizure (Schevon et al, 2012). The real high frequency unit response occurred in a delayed manner during seizure spread without apparent change in the low frequency signal, implying that the typical oscillatory phenomena recorded in the classical EEG reflect only the inhibitory synaptic barrages.…”
Section: Neuronal Firing Patterns In Epileptic Cortexsupporting
confidence: 50%
“…SUA activities during ictal events were also less hypersynchronous as was previously hypothesized (Babb et al, 1987;Truccolo et al, 2011). Detailed analysis of ictal unit firing revealed the presence of an inhibitory wave local to the seizure onset zone , suggesting that inhibitory input may prevent the spread of the seizure (Schevon et al, 2012). The real high frequency unit response occurred in a delayed manner during seizure spread without apparent change in the low frequency signal, implying that the typical oscillatory phenomena recorded in the classical EEG reflect only the inhibitory synaptic barrages.…”
Section: Neuronal Firing Patterns In Epileptic Cortexsupporting
confidence: 50%
“…In this study of unit activity performed with tetrode electrodes, the decrease in firing gener- ated by principal neurons was preceded by an increase in the activity of units identified as inhibitory interneurons. A reduction of unit activity at seizure onset was seen also in multiunit studies performed during presurgical intracranial monitoring in drug-resistant patients with partial epilepsy (Truccolo et al 2011;Bower et al 2012;Schevon et al 2012), suggesting that dampening of neuronal firing at the very beginning of a partial seizure occurs in epileptic patients as well.…”
Section: Seizure Onsetmentioning
confidence: 91%
“…These data suggest that the low-voltage fast activity seen in the EEG at the beginning of focal seizures correlates with an arrest of principal cell firing possibly reflecting enhanced inhibition in the epileptogenic region. In addition, Schevon et al 17 have demonstrated irregular and relatively low level of unit firing at the onset of ictal activity in patients with focal epilepsy; this phenomenon was interpreted by these authors as an inhibitory restraint that prevents the spread of the ictal discharge (see subsequent text).…”
Section: Initiation Of Focal Seizuresmentioning
confidence: 99%
“…For instance, Trevelyan and colleagues 17,56 proposed that GABAergic activation represents an inhibitory restraint occurring ahead of the ictal excitatory wave and thus opposes the generation of epileptiform activity. This interpretation, however, rests on the nonverified assumption that excitatory-based ictal discharges have already started somewhere else (as in the model of focal seizures induced by local N-methyl-D-aspartate (NMDA) applications 57 ) and on the presumption that GABA receptor signaling has a compensatory (reparative) function rather than an active role in seizure generation as reviewed earlier.…”
Section: A New Model For Focal Ictogenesismentioning
confidence: 99%